TV viewing relationship with values - a field study - Tedjani BENTAHAR; Miloud ABDELFATAH (Social Sciences Journal, 1970)
The relationship of television viewing with values has become one of the factors influencing the formation of values and attitudes among members of the same society in view of its effective role in social change. Therefore, we want to shed light on the features and nature of the relationship again to the direction of the existing between each of the television viewing being one of the forms of media, as well as the nature of the values that the individual has, and the media has a role in that.